Quality improvement in paediatric radiation oncology through peer review. Issue 5 (27th July 2020) - Murphy, Laura; Cantwell, Jessica; Chard, Jennifer; Cheuk, Robyn; Harrington, Christopher; Hindson, Ben; Salkeld, Alison; Saran, Frank; Wheeler, Greg; Wiltshire, Kirsty; Ahern, Verity
Abstract: Introduction: Around 300 children in Australia and New Zealand (ANZ) undergo a course of radiation treatment (RT) each year. A fortnightly videoconference for radiation oncologists managing children started in 2013. We conducted an audit of the videoconference to assess its influence on the care of children who receive RT in ANZ. Methods: De‐identified data from minutes (August 2013–December 2019) were analysed retrospectively using three categories: meeting participation, case presentations and management decisions. Results: There were 119 meetings and 334 children discussed over the six‐year audit period with regular attendance from four of 11 centres treating children in ANZ. Most cases (80%) were discussed prior to RT. A change in the overall management plan was recommended for around one in eight patients (35/334, 13%). RT plan reviews were performed in 79 cases (23%). Adjustments were made to the target volume contours or treatment plan in 8% (6/79). Conclusion: Increasing the frequency of the meeting to weekly and compliant with the RANZCR Peer Review Audit Tool has the capacity to review all paediatric RT patients in ANZ prior to RT and initiate changes for as many as one in eight children treated by RT each year. The meeting should be considered a core component necessary to maintain expertise in paediatric RT in all centres providing RT for children in ANZ while also acting as a proton referral panel as more children are referred abroad for proton therapy before the Australian Bragg Centre for Proton Therapy opens in Adelaide in 2024.